Aplikasi Pembelajaran Interaktif Berbasis Multimedia Untuk Sekolah Dasar (Studi Kasus : SD Negeri I Bitung, Kelas VI) - Mudiyanto Setiawan; Arie S.M. Lumenta; Virginia Tulenan (Universitas Sam Ratulangi, 2017)
Abstract - Multimedia is a technology concept to present information, which consists of a combination of images, sound, animation and video. Multimedia development is now widely used in the scope of business, education, and government agencies. Learning media is a tool that enables easy interaction educators and students in a process of learning.Learning system that is currently used in primary schools are still using conventional learning media. This perceived lack of interest and understanding of students in school learning material capture.Application-Based Multimedia Interactive Learning is a multimedia application that runs with the help of computers built to help increase interest and understanding of students to learn. Applications created using Adobe Flash CS5 software and language Action Script. The research methodology used to adapt the systems development methodology version of Luther-Sutopo with stage Concept, Design, Material Collecting, Assembly, Testing and Distribution.Based on the analysis of the development of systems using the methodology of the Luther-generated Sutopo Interactive Learning Based Multimedia Applications containing materials and exercises by the standards of competence curriculum that goes with the material limits to sixth grade elementary school science lessons.Keywords: Adobe Flash CS5, Application of Learning, Interactive, Methodology of Luther-Sutopo, MultimediaAbstrak - Multimedia adalah suatu konsep teknologi untuk menyajikan informasi, yang terdiri dari gabungan gambar, suara, animasi dan video. Perkembangan multimedia saat ini telah banyak digunakan dalam lingkup usaha, pendidikan, maupun instansi pemerintahan. Media pembelajaran merupakan alat bantu yang mempermudah interaksi pendidik dengan siswa dalm proses belajar mengajar. Sistem pembelajaran yang saat ini digunakan pada sekolah dasar masih menggunakan media pembelajaran konvensional. Hal tersebut dirasa kurang menarik minat dan pemahaman siswa dalam menangkap materi pembelajaran disekolah.Aplikasi Pembelajaran Interaktif Berbasis Multimedia merupakan aplikasi multimedia yang berjalan dengan bantuan komputer yang dibangun untuk membantu meningkatkan minat dan pemahaman siswa dalam belajar. Aplikasi dibuat menggunakan software Adobe Flash CS5 dan bahasa Action Script. Metodologi penelitian yang digunakan mengadaptasi metodologi pengembangan sistem versi Luther-Sutopo dengan tahapan Concept, Design, Material Collecting, Assembly, Testing dan Distribution. Berdasarkan analisa pengembangan sistem menggunakan metodologi Luther-Sutopo tersebut dihasilkan Aplikasi Pembelajaran Interaktif Berbasis Multimedia yang berisi materi-materi dan soal latihan berdasarkan standar kompentensi kurikulum yangÂ berjalan dengan batasan materi untuk pelajaran IPA kelas VI SD.Â Kata Kunci: Adobe Flash CS5, Aplikasi Pembelajaran, Interaktif, Metodologi Luther-Sutopo, Multimedia